Guest Editorial-Special Section for Selected Papers from ISCAS 2007 - Lian, Yong; Sawan, Mohamad (IEEE transactions on biomedical circuits and systems, 2008)
The four papers in this special section are from the 2007 IEEE International Symposium on Circuits and Systems (ISCAS 2007), that was held in New Orleans, LA, on May 20-27, 2007. The selected papers reflect continuing trends toward higher levels of biomedical circuits and systems covering a wide variety of subjects within the analog and RF integrated circuits and signal processing fields, ranging from mixed-signal building blocks to system applications on several related biomedical applications.